Habitat structure modifies microclimate: An approach for mapping fine‐scale thermal refuge. Issue 6 (24th April 2018) - Milling, Charlotte R.; Rachlow, Janet L.; Olsoy, Peter J.; Chappell, Mark A.; Johnson, Timothy R.; Forbey, Jennifer S.; Shipley, Lisa A.; Thornton, Daniel H.
Abstract: Contemporary techniques predicting habitat suitability under climate change projections often underestimate availability of thermal refuges. Habitat structure contributes to thermal heterogeneity at a variety of spatial scales, but quantifying microclimates at organism‐relevant resolutions remains a challenge. Landscapes that appear homogeneous at large scales may offer patchily distributed thermal refuges at finer scales. We quantified the relationship between vegetation structure and the thermal environment at a scale relevant to small, terrestrial animals using a new approach for mapping fine‐scale thermal heterogeneity. We expected that vegetation would create attenuated microclimates and that the influence of vegetation structure would vary seasonally. We measured shrub volume, horizontal cover and operative temperature ( T e ) in a sagebrush‐steppe habitat in Idaho, USA, at 534 microsites across two study sites of c . 1 km 2 each. We modelled relationships between habitat structure and both mean daily maximum temperature ( T ¯ max ) and mean diurnal temperature range ( DTR ¯ ) for each study site during summer and winter. Aerial imagery from unmanned aerial systems was used to estimate shrub volume and canopy cover at 1‐m resolution, and we applied the best fit model to map thermal heterogeneity across broader extents. Increasing shrub volume and cover was associated with lower T ¯ max and DTR ¯, but strengths of the relationships differed between study sites. There was considerable heterogeneity in availability of thermal refuges across sagebrush‐steppe rangelands that have traditionally been considered relatively homogeneous. This technique can help ecologists and land managers identify critical thermal refuges that large‐scale climate modelling can overlook and thus contribute to an understanding of animal–habitat relationships under changing climates and land uses.